2015
DOI: 10.11158/saa.20.5.4
|View full text |Cite
|
Sign up to set email alerts
|

<p><strong>Effects of temperature on development and reproduction of <em>Neoseiulus bicaudus</em> (Phytoseiidae) feeding on <em>Tetranychus turkestani</em> (Tetranychidae)</strong></p><p><strong><em><br /></em></strong></p>

Abstract: Neoseiulus bicaudus (Wainstein), a species of Neoseiulus Hughes (Acari: Phytoseiidae), was collected at Ili in the Xinjiang Uyghur Autonomous Region of China in July 2013. As Neoseiulus species are valuable predator mites, N. bicaudus could be used for biocontrol of some small pests like spider mites, whitefly, and thrips. Tetranychus turkestani (Ugarov et Nikolskii) is the main spider mite affecting agriculture and forestry in Xinjiang. The development rate and reproductive biology of N. bicaudus feeding on T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Within the above range of higher temperature then, the developmental period increases with increasing temperature. Studies have reported that in the suitable temperature range, the length of the immature stage will gradually shorten as the temperature increases 56 . Conversely, the developmental duration of the insect was prolonged when the ambient temperature was elevated to an unsuitable temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Within the above range of higher temperature then, the developmental period increases with increasing temperature. Studies have reported that in the suitable temperature range, the length of the immature stage will gradually shorten as the temperature increases 56 . Conversely, the developmental duration of the insect was prolonged when the ambient temperature was elevated to an unsuitable temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Since mites were removed on each capture to enable identification, the increase in mites in the study reflects an increase in new individual mites entering the lizard population (not just recounting the same individual mites). Mesostigmatid mite lifecycles are often affected by temperature and humidity (Ganjisaffar et al ., 2011; Li et al ., 2015), where warmer temperatures and higher humidity favours faster development in Dermanyssus gallinae up to a point where extreme temperatures or low humidity is lethal (e.g. Nordenfors et al ., 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This species completes its development between 18–35°C; the optimal temperature for N . bicaudus reproduction and development is ~26°C (Li et al, 2015). N .…”
Section: Introductionmentioning
confidence: 99%
“…Thrips tabaci Lindeman (Thysanoptera: Thripidae), Tetranychus turkestani Ugarov et Nikolski (Acari: Tetranychidae), and T. truncatus Ehara (Acari: Tetranychidae) on crops and vegetables (Han et al, 2020;Su et al, 2019;Zhang et al, 2017). This species completes its development between 18-35°C; the optimal temperature for N. bicaudus reproduction and development is ~26°C (Li et al, 2015). N. bicaudus can be mass-reared using Tyrophagus putrescentiae Schrank (Acari: Acaridae) as a food source (Su et al, 2019).…”
mentioning
confidence: 99%